THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, INTRINSIC MOTIVATION ON EMPLOYEE PERFORMANCE WITH WORK FACILITY AS A MEDIATION VARIABLE - KHOIRUNNISA, DESTY (JOURNAL OF RESEARCH IN MANAGEMENT, 2019)
The purpose of this study was to analyze the effect of transformational leadership style,intrinisk motivation on the performance of employees train company with job satisfaction asa mediating variable. The number of respondents taken in this study were 52 respondentsusing probability sampling. This study uses a survey method using a quantitative approach.The analytical tool used in this study is multiple regression analysis with SPSS software.Based on the conclusion that transformational leadership style and intrinsic motivation havea positive effect on employee performance with job satisfaction as a mediating variable.